Two molecular markers based on mitochondrial genomes for varieties identification of the northern snakehead (Channa argus) and blotched snakehead (Channa maculata) and their reciprocal hybrids. (August 2015) - Xincheng, Zhang; Kunci, Chen; Xinping, Zhu; Jian, Zhao; Qing, Luo; Xiaoyou, Hong; Wei, Li; Fengfang, Xiao
Abstract The northern snakehead (Channa argus) and blotched snakehead (Channa maculata) and their reciprocal hybrids have played important roles in the Chinese freshwater aquaculture industry, with an annual production in China exceeding 400 thousand tons. While these are popular aquaculture breeds in China, it is not easy to identify northern snakehead, blotched snakehead, and their hybrids. Thus, a method should be developed to identify these varieties. To distinguish between the reciprocal hybrids (C. argus ♀ × C. maculata ♂ and C. maculata ♀ × C. argus ♂), the mitochondrial genome sequences of northern snakehead and blotched snakehead and their reciprocal hybrids were compared. Following the alignment and analysis of mtDNA sequences of northern snakehead, blotched snakehead and their hybrids, two pairs of specific primers were designed based on identified differences ranging from 12S rRNA to 16S rRNA gene. The BY1 primers amplified the same bands in the blotched snakehead and the hybrid (C. maculata ♀ × C. argus ♂), while producing no products in northern snakehead and the hybrid (C. argus ♀ × C. maculata ♂). Amplification with WY1 yielded the opposite results. Then, 30 individuals per fish were randomized to verify the primers, and the results showed that the primers were specific for breeds, as intended. The specific primers can not only simply distinguish between two kinds of hybrids, but also rapidly identify the two parents. This study provides a method of molecular marker identification to identify reciprocal hybrids.